Serviço social e educação no Brasil: limites e desafios do trabalho profissional - Rodrigues, Geyzon Cosme Santos (2022)
The insertion of social workers in education policy dates back to the first decades of the 20th century, scenarios in which the first schools of Social Work emerged in Brazil. During this century, the profession underwent several reconceptualization processes, resulting from political, economic, social and cultural, national and international changes, which were able to remodel its theoretical-methodological matrices and professional work with the working classes. This research sought to investigate the foundations of the social worker's work, based on the knowledge produced by the profession. The time frame delimited was from works published between the years 2000 and 2020. This period was a milestone in the creation of social policies, which contributed to a greater expansion of social workers in the scope of public policies, especially in education: with a strong focus on the University education. The prism of critical social theory was considered to examine the processes that involve the object of this research. In the development of this work, the modality of documental research and bibliographic research was launched, involving the state of the art on the subject. The sources researched were indexed journals in the area of Social Work in Brazil, focusing on Qualis A1 and A2, such as: Serviço Social & Sociedade, Katálysis, Em Pauta, Ser Social and Textos & Contextos. The research result showed at least four trends present in the work of social workers in education. The first deals with the primary inter/disciplinary work on the singularities and unitary decisions of professionals; and has strong corporate work characteristics. The second tendency is related to the professional's identification with the educational/pedagogical work, in which sometimes he mortgages the pedagogical to teachers, sometimes he crystallizes everything that is educational as good. The third, and last, is the subsumption of the technical to the theoretical and ethical. With this, it was found that, like the emergence in the early years of the twentieth century, Social Work and the way of thinking of social workers still keep latent the regulatory and control practices of behavior of subjects of social policies. We recognize that we have advanced a lot in terms of social context, number of professionals in social policies, but forms of social regulation are still perennial. Considering social reality as something dynamic, procedural and contradictory, understanding and combating these elements of conservatism requires everyone's attention, studies, research and attitudes.